'But nobody talks to accountants': the growing influence of the finance department in the advertising agency. (2nd January 2020) - Crawford, Robert
ABSTRACT: Historical scholarship on the advertising industry has largely focused on advertisements that it creates and, to a lesser degree, the agency's relationship with clients. This focus has meant that the finance department and its contribution to the agency's operations have largely been ignored. This article seeks to address this omission by drawing attention to the work and contribution of the finance department in the advertising agency setting. It focuses on experiences of two trained accountants, who worked for George Patterson, one of Australia's largest advertising agencies. Lincoln Farnsworth helped build George Patterson from the 1930s to the 1960s, while Russell McLay emerged as a key player in the agency's subsequent expansion and internationalisation in the 1970s and 1980s. By using oral history testimony and other documentary materials, this article illustrates the growing impact of accounting on advertising agency practices and the advertising business, and highlights the contribution that accounting history offers to historians working in other fields.